AGED PEOPLE'S PERCEPTION ABOUT THE TRANSITIONAL CARE PROVIDED BY A MULTIPROFESSIONAL HOME-BASED ASSISTANCE TEAM - Jeane Roza Quintans; Marta Maria Melleiro (Cogitare Enfermagem)
Objective: to understand the aged people's perception about the care provided by a Multiprofessional Home-based Assistance Team in the city of São Paulo - Brazil.